2008
DOI: 10.1155/2008/932632
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ, PTEN, and the Fight against Cancer

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-activated transcription factor, which belongs to the family of nuclear hormone receptors. Recent in vitro studies have shown that PPARγ can regulate the transcription of phosphatase and tensin homolog on chromosome ten (PTEN), a known tumor suppressor. PTEN is a susceptibility gene for a number of disorders, including breast and thyroid cancer. Activation of PPARγ through agonists increases functional PTEN protein levels that subsequently ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Previous investigations have indicated that pancreatic cancer growth can be modulated by PTEN regulating agents such as TGF-beta (38) and PPAR-gamma PTEN (39). Our results show that BITC did not alter the protein or phosphorylated levels of PTEN in either BxPC-3 or PanC-1 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have indicated that pancreatic cancer growth can be modulated by PTEN regulating agents such as TGF-beta (38) and PPAR-gamma PTEN (39). Our results show that BITC did not alter the protein or phosphorylated levels of PTEN in either BxPC-3 or PanC-1 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The data are therefore consistent with the notion that SSc fibroblasts possess a gene expression signature reminiscent of TGFb signaling , but are activated in a fashion that is autonomous of canonical TGFb signaling but dependent on non-canonical TGFb signaling pathways (Trojanowska, 2009;Leask, 2011). One possible mechanism underlying the reduced PTEN expression in SSc fibroblasts could be due to reduced expression of peroxisome proliferator-activated receptor-g; peroxisome proliferator-activated receptor-g is reduced in SSc fibroblasts; and peroxisome proliferator-activated receptor-g can regulate PTEN expression (Teresi and Waite, 2008;Wei et al, 2010). Our data collectively suggest that PTEN normally suppresses fibrogenesis in vivo and that loss of PTEN expression is sufficient for fibrogenesis in vivo.…”
Section: Loss Of Pten Results In Fibrosismentioning
confidence: 99%
“…PPARγ has been suggested as a tumor suppressor in human follicular thyroid cancer (Shen and Chung, 2005; Teresi and Waite, 2008). PPARγ was shown to suppress proliferation and increase apoptosis of thyroid tumor cells by activating nuclear factor-κB signaling (Kato et al ., 2006).…”
Section: Resultsmentioning
confidence: 99%